2018
DOI: 10.1055/s-0038-1675602
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Severity in Patients on Non-Vitamin K Antagonist Oral Anticoagulants with a Standard or Insufficient Dose

Abstract: Background The stroke severity or functional outcomes could differ because the efficacy of non-vitamin K antagonist oral anticoagulants (NOACs) could be different according to the dose. We investigated whether there was any difference in the stroke outcomes in patients with non-valvular atrial fibrillation (NVAF) by their prior medication status, including standard-dosed versus under-dosed NOACs. Materials and Methods We enrolled 858 patients with acute ischaemic stroke with chronic NVAF admitted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
2
11
3
Order By: Relevance
“…et al pointed out that off-label rivaroxaban was associated with an increased risk of ischemic stroke with 2.75 times [6]. The standard dose NOACs was associated with a relatively mild stroke in the patients compared to under-dosed NOACs [13]. The previous studies were similar to our study which showed a poor clinical bene t of off-label anti-coagulation.…”
Section: Discussionsupporting
confidence: 89%
“…et al pointed out that off-label rivaroxaban was associated with an increased risk of ischemic stroke with 2.75 times [6]. The standard dose NOACs was associated with a relatively mild stroke in the patients compared to under-dosed NOACs [13]. The previous studies were similar to our study which showed a poor clinical bene t of off-label anti-coagulation.…”
Section: Discussionsupporting
confidence: 89%
“…In patients with NVAF who suffer an ischemic stroke, stroke outcome has been shown to differ according to the activity of oral anticoagulants [9]. Notably, specific coagulation tests, including diluted thrombin time and chromogenic anti-Xa assays, have demonstrated a strong correlation with plasma concentrations of direct oral anticoagulants (DOACs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, along with the risk of adverse events, off-label underdosed NOAC was also associated with increased stroke severity than that of on-label standard doses or warfarin given at a therapeutic intensity. 46) Overall, previous studies consistently showed that the use of off-label underdosed NOACs attenuated the benefit of NOACs over warfarin.…”
Section: Clinical Impact Of Off-label Dosing Of Noacsmentioning
confidence: 83%